THROMBOTIC MICROANGIOPATHY IN THE PATHOGENESIS OF OBSTETRIC COMPLICATIONS - S. V. Akinshina; V. O. Bitsadze; Z. K. Gadaeva; A. D. Makatsariya (IRBIS LLC, 2016)
Thrombotic microangiopathy is one of the most serious thrombotic complications characterized by microvascular thrombosis in various organs and accompanied by thrombocytopenia and hemolytic anemia. The term thrombotic microangiopathy has incorporated several nosology, which are characterized by different mechanisms of microvascular thrombosis. Currently thrombotic microangiopathy include thrombotic thrombocytopenic purpura (TTP), hemolytic uremic syndrome (HUS), heparin-induced thrombocytopenia, HELLP-syndrome. Pregnancy presents one of the key triggers to the development of thrombotic microangiopathy. This fact gives us a significant opportunity to study the pathogenesis of thrombotic microangiopathy in the context of the physiological changes of hemostasis during pregnancy. At the same time the discovery of molecular mechanisms of thrombotic microangiopathy allows for a new research on the field of pathogenesis of thrombotic complications associated with pregnancy, as well as the pathogenesis of so-called placental obstetric complications, including severe preeclampsia, premature detachment of normally situated placenta, septic shock.